Prinsip Ta'awun dalam praktis keadilan gender menurut Islam - Fatin Maziyyah Ja'far,; Wan Fariza Alyati Wan Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The gender equality that the West is fighting for does not provide a firm foundation for the relationship between men and women. Unlike the concept of gender justice brought by Islam, where Islam has positioned different roles for men and women where the roles correspond to the advantages they have. The concept of ta'awun (cooperation) is applied to complement the relationship between men and women in all aspects of life. Furthermore, this study was conducted to provide a clear understanding of the concept of gender justice according to Islam and to position ta'awun as the primary foundation in the relationship between men and women. The study uses a qualitative method by collecting and analyzing relevant documents. The findings of the study show that gender justice according to Islam is more flexible and practical to apply in all aspects. Moreover, the concept of ta'awun applied in gender justice between men and women can form a pattern of harmonious community because the relationship between man and woman is not seen from the differences of position and role and is not subject to any discrimination.